Effects of diaphragmatic breathing and body composition of the recovery of male collegiate taekwondo kyorugi athletes - Cambas, John Clarence D.
Optimal recovery during the breaks in between rounds of a Taekwondo Kyorugi event is very important in order to perform efficiently in the next round. It is observed in competitions that different athletes have different recovery techniques, breathing patterns and resting positions This study aims to compare and determine the most efficient recovery position by comparing their recovery by measuring the heart rate and evaluating themselves through the Perceived Recovery Status Scale after resting in the 4 body positions (standing, sitting, hands on knees, and lying down) for I minute after 2 minutes of Taekwondo kicking and footwork drills. The present study’s results show a significant difference between the four body positions. Based on the mean recovery heart rate of the four body positions the order of increasing recovery heart rate is lying down > sitting > standing > hands on knees, with lying down having the highest recovery. Multiple studies show similar results stating that lying supine is most effective for heart rate recovery linking it to less gravitational force acting on the heart and accelerated